Comprehending Human Economic Behavior Through a Multicultural Lens: Examining the Concepts of Homo Economicus and Islamicus - Lahuri, Setiawan bin; Labolo, Sultan Nanta Setia Dien (Kawanua International Journal of Multicultural Studies, 2023)
Homo economicus and homo islamicus are two concepts of human economic behavior that stem from different intellectual backgrounds. This paper aims to conduct a critical comparative analysis on the fundamental assumptions of the two concepts. The research method is qualitative, drawing upon key literature from Western and Islamic schools of thought. The results show that homo economicus and homo islamicus differ significantly in terms of underlying principles, motivations, and moral considerations. Homo economicus is driven by self-interest and narrow rationality, while homo islamicus is guided by the framework of Islamic values. These differences have implications on how the two concepts view systems of production, consumption, and distribution. However, the concepts can complement each other in providing a more comprehensive understanding of human economic behavior. The study suggests the need for integrating or synthesizing diverse perspectives in formulating a multidimensional and culturally inclusive analytical framework of economic behavior.